Digital Prime and Forensic science in cyberspace - Michelle Potter (Idea Group Publishing, 2006)
This chapter gives an overview of the major types of electronic attacks encountered today and likely to continue into the foreseeable future. A comprehensive understanding of attackers, their motives, and their methods is a prerequisite for digital crime investigation. The range of possible cyber attacks is almost unlimited, but many attacks generally follow the basic steps of reconnaissance, gaining access, and cover-up. We highlight common methods and tools used by attackers in each step. In addition, attacks are not necessarily directed toward specific targets. Viruses, worms, and spam are examples of large-scale attacks directed at compromising as many systems as possible.